第1题 3x(x-1)=2-2x
第2题(2x+3)²=4(2x+3)
第3题 2(x-3)²=x²-9
第1题 3x(x-1)=2-2x
第2题(2x+3)²=4(2x+3)
第3题 2(x-3)²=x²-9
一、3x(x-1) = 2-2x ; 3x(x-1)-2(1-x)=0 ; (3x+2)(x-1)=0 ; x=1 或 x=-2/3
二、右边移过来得到 (2x+3-4)(2x+3)=0 ;x=1/2 或 x=-3/2
三、等式右边化成(x+3)(x-3)再移到左边提取得(x-3)(2x-6-x-3)=0 ;x=3或x=9
希望采纳
1. 3x(x-1)=2-2x
3x^2-3x=2-2x
3x^2-x-2=0
(3x+2)(x-1)=0
2.(2x+3)²=4(2x+3)
4x^2+12x+9=8x+12
4x^2+4x-3=0
(2x-1)(2x+3)=0
3. 2(x-3)²=x²-9
2(x-3)^2=(x-3)(x+3)
1.3x(x-1)-2(x-1)=0 (x-1)(3x-2)=0 x=1或者x=三分之二
2.(2x+3)(2x+3-4)=0 x=负二分之三或者x=二分之一
3.(x-3)(2(x-3)-(x+3))=0 x=3或者x=9
3x(x-1)=2-2x
3x^2-3x=2-2x
3x^2-x-2=0
(3x+2)(x-1)=0
x=-2/3或1
(2x+3)²=4(2x+3)
(2x+3)(2x+3-4)=0
x=-3/2或1/2
2(x-3)²=x²-9
2x^2-12x+18=x^2-9
x^2-12x+27=0
(x-3)(x-9)=0
x=3或9
3x(x-1)=2-2x =2(1-X)
所以3X=1-x
x=0.25
(2x+3)²=4(2x+3)
所以2X+3=4
X=0.5
2(x-3)²=x²-9
2(x-3)²=(X-3)(X+3)
所以2(X-3)=X+3
X=9